Influence of nutrition on breast cancer: a review (Research, Society and Development, 2022)
Nutrition is one of the main collaborators in the restoration of breast neoplasms. Given that breast cancer is one of the diseases that most often manifests itself in women. The number of cases has been growing every year due to the various factors that trigger it, whose bad eating habits is what stands out the most, where the intake of a diet high in fat and low in dietary fiber contribute to the development of breast neoplasia. On the other hand, a diet that focuses on a greater intake of foods rich in fiber, vitamins, protein and antioxidants, help in the physiological control of the body by increasing its immunity. Food represents a potential prevention factor in the development of this neoplasm, given that all food consumed has macronutrients and micronutrients that help fight and destroy malignant cells. Prevention of overweight and obesity is one of the main strategies for the Prevention of breast cancer. Since maintaining healthy food habits, based on fruits, vegetables, vegetables, whole grains and legumes, and staying physically active with regular physical exercise practices in conjunction with a balanced diet, can modify the process of carcinogenesis, especially in the initial phase, providing better results in treatment.